Financial Information Transparency and Firm Performance in China - Wang, Qiannan (2017)
This study examines the financial effects of information transparency on firm profitability and the firm value of two hundred Chinese listed firms from 2014 to 2016. It differs from current research in China, which normally uses the disclosure and transparency rankings to represent enterprise information transparency, by adopting the degree of earnings management as a proxy for financial information transparency in this study, which is the absolute value of discretionary accruals. The results show that financial information transparency is negatively related to firm value and does not impact firm profitability significantly.